“Giving Faith” to Everyday Catastrophe: the Multidimensionality of Events - Souza Leal, Bruno (2024)
In this article, we discuss the everyday and relational character of catastrophe, which makes the term extrapolate its association with specific events. For this, we take as reference a particular social reality that, being singular and geographically delimited – a garbage dump in Iguatu (Ceará, Brasil) –, finds similarities and adversities with several others existing in different Brazilian cities and even in different countries. With it, we observe that disasters are circumscribed to territorialities and to the ways of seeing and relating to the place, so that it takes place in specific social situations, which it is possible to live with on a daily basis.